Computer modeling of acoustical elements of a hearing aid - Szwoch, G.; Kostek, B.; Czyżewski, A. (Archives of Acoustics, 2001)
In this paper, application of computer modeling methods to the process of hearing aid fitting is described. A computer model of the acoustical system of a hearing aid is presented. Exemplary results of the experiments are presented and compared with measurement data. The model proved to behave similarly to the physical system. Further improvements to the model are discussed.